Disgust sensitivity relates to attitudes toward gay men and lesbian women across 31 nations. (April 2023) - van Leeuwen, Florian; Inbar, Yoel; Petersen, Michael Bang; Aarøe, Lene; Barclay, Pat; Barlow, Fiona Kate; de Barra, Mícheál; Becker, D. Vaughn; Borovoi, Leah; Choi, Jongan; Consedine, Nathan S.; Conway, Jane Rebecca; et al.
Previous work has reported a relation between pathogen-avoidance motivations and prejudice toward various social groups, including gay men and lesbian women. It is currently unknown whether this association is present across cultures, or specific to North America. Analyses of survey data from adult heterosexuals ( N = 11, 200) from 31 countries showed a small relation between pathogen disgust sensitivity (an individual-difference measure of pathogen-avoidance motivations) and measures of antigay attitudes. Analyses also showed that pathogen disgust sensitivity relates not only to antipathy toward gay men and lesbians, but also to negativity toward other groups, in particular those associated with violations of traditional sexual norms (e.g., prostitutes). These results suggest that the association between pathogen-avoidance motivations and antigay attitudes is relatively stable across cultures and is a manifestation of a more general relation between pathogen-avoidance motivations and prejudice towards groups associated with sexual norm violations.